2020
DOI: 10.4082/kjfm.18.0129
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hand Grip Strength and Cardiometabolic Markers in Korean Adult Population: The Korea National Health and Nutrition Examination Survey 2015-2016

Abstract: See editorial commentary page on 271 Background: Muscle strength has been suggested as a cardiovascular marker. The aim of this study was to examine the associations between hand grip strength and biomarkers of cardiovascular disease in the Korean population. Methods: A total of 9,083 participants aged 20-80 years from Korea National Health and Nutrition Examination Survey 2015-2016 were investigated. Results: Among men, both relative and dominant hand grip strength showed a positive association with diastolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
5
15
0
1
Order By: Relevance
“…악력은 근력을 대표하는 지표 중 하나로써 [15,16], 대사성 질환의 유병 률 및 발병률과 높은 관계성이 있는 것으로 보고되고 있다 [17][18][19][20][21][22][23][24][25] [17,19,21,23] 또는 절대 악력과 관련성이 있음을 제시한다 [20].…”
unclassified
“…악력은 근력을 대표하는 지표 중 하나로써 [15,16], 대사성 질환의 유병 률 및 발병률과 높은 관계성이 있는 것으로 보고되고 있다 [17][18][19][20][21][22][23][24][25] [17,19,21,23] 또는 절대 악력과 관련성이 있음을 제시한다 [20].…”
unclassified
“…15) However, Ho et al, 16) revealed that both the abso-lute and relative grip strengths had similar predictive abilities for cardiovascular disease and all-cause mortality. 16) Using the KNHANES 2015-2016, Chong et al 17) assessed the association between the absolute and relative grip strengths and cardiometabolic outcomes in a Korean adult population stratified by sex and age. Grip strength measurements could be affected by the protocol used.…”
mentioning
confidence: 99%
“…Therefore, Chong et al 17) used the Southampton protocol to measure handgrip strength (HGS) following the suggestion of Roberts et al 13) Chong et al 17) revealed that grip strength has a Thus, grip strength could be used as a biomarker of healthy aging for people of all ages and may be an effective screening…”
mentioning
confidence: 99%
See 2 more Smart Citations